Design and Construction of Small Power Boost Converter with Educational and Research Purposes - D"™Alessio, L. A.; González, L. G.; Cáceres, R. O. (ACI Avances en Ciencias e Ingenierías, 2014)
This paper presents the design and construction of a DC-DC boost converter for a nominal power of 200W, with an input voltage of 100V and an output voltage of 200V, on the basis of theoretical analysis with the aim of design and determine all the components associated with the mentioned converter. In this research we use the voltage feedback control with a PI controller tuned by pole placement, and a PWM modulator for the IGBT switching. The converter performance and the control system faced with step changes in the input voltage and the load resistance is verified through computer simulation and then verified by experimental tests using a microcontroller PIC16F877.